2016
DOI: 10.18662/po/2016.0701.07
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Job Strain with Psychological Hardiness, Organizational Support, Job Control and Work Overload: An Evaluation of Karasek’s DCS Model

Abstract: This study focused on the investigation of how personal and situational factors and work related outcomes are associated. The study was built on "Karasek's Model of Job Strain" called as DCS Model (Demand-Control-Support). It is aimed to assess how psychological hardiness, organizational support, job control and work overload are related with perceived job strain. In order to test the propositions of the study, an empirical study was performed in Turkey among the employees working in banking & finance organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…This indicated that RC among academics engendered high levels of WT. Given that earlier studies by Tastan (2016) and Abuaddous et al (2015) found RC to have a positive impact on WT, it was not surprising that this study found RC to have a significant impact on WT.…”
Section: Regression Analysissupporting
confidence: 46%
“…This indicated that RC among academics engendered high levels of WT. Given that earlier studies by Tastan (2016) and Abuaddous et al (2015) found RC to have a positive impact on WT, it was not surprising that this study found RC to have a significant impact on WT.…”
Section: Regression Analysissupporting
confidence: 46%
“…Despite the unsupported direct association of mindfulness, this research found that the trait of psychological hardiness mediated the association between mindfulness and emotional exhaustion fully. This association between psychological hardiness and emotional exhaustion adds further support to previous research, which has shown that psychological hardiness is a trait that is particularly important in helping individuals overcome stressful situations (Abdollahi et al ., 2018; Faiz, 2018; Nguyen et al ., 2012; Taştan, 2016). Overall, the result of the mediating effect analysis implied that mindfulness may reduce emotional exhaustion by promoting psychological hardiness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Abdollahi, Carlbring, Vaez and Ghahfarokhi (2018) found that psychologically hardy individuals can manage their emotions effectively, and thereby overcome stressful situations encountered in their career path. Psychological hardiness also allows individuals to cope better with negative circumstances in life and at work (Taştan, 2016). For example, Faiz (2018) argued that it buffers individuals from the adverse effects of internal workplace politics and incivility.…”
Section: Introductionmentioning
confidence: 99%
“…Work overload is defined as the employees' perception of numerous job tasks or lack of adequate time to finish these tasks (Mansour & Tremblay, ). On the basis of this approach, work overload can be described as the perception of employees regarding the available resources such as time, energy, and ability to respond and fulfill the assigned tasks, as well as managers and supervisors' expectations (Bal Taştan, ). Among the employees of travel agencies, work overload is positively associated with pressure, stress, and turnover intention, whereas it is negatively associated with organizational citizenship behavior, commitment, work engagement, and job embeddedness (Karatepe, ; Karatepe & Uludag, ; Lin et al, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%